1993
DOI: 10.1021/jf00030a023
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 2-acetyl-1-pyrroline to odors from wetted ground pearl millet

Abstract: The odorous compound 2-acetyl-1-pyrroline (2AP) was the cause of an undesirable "mousy" odor that developed when raw pearl millet grits were wetted and slowly dried. The 2AP in millet was identified by comparing gas chromatography (GC) retention times, odor at the GC sniffing port, mass spectra, and vapor-phase infrared spectra with those of 2AP from Jasmine and Indian Basmati aromatic rices. Identification of 2AP in aromatic rices had been reported previously. The odor of 2AP at the sniffing port was similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…2-acetyl-1-pyrroline, a "popcorn"-like flavor compound was reported as the main flavor component of aromatic rice 1,2 . Also this compound contributed to the "roasted aroma" of cooked beef, crusts of wheat and rye breads 10 , popcorn 9 , and wetted ground pearl millets 8 "aroma" quality of aromatic rice in sensory evaluation showed strong correlation to its content 7 . We previously reported that 2-acetyl-1-pyrroline did not form during cooking or postharvest processing of aromatic rice varieties 12 .…”
Section: Introductionmentioning
confidence: 93%
“…2-acetyl-1-pyrroline, a "popcorn"-like flavor compound was reported as the main flavor component of aromatic rice 1,2 . Also this compound contributed to the "roasted aroma" of cooked beef, crusts of wheat and rye breads 10 , popcorn 9 , and wetted ground pearl millets 8 "aroma" quality of aromatic rice in sensory evaluation showed strong correlation to its content 7 . We previously reported that 2-acetyl-1-pyrroline did not form during cooking or postharvest processing of aromatic rice varieties 12 .…”
Section: Introductionmentioning
confidence: 93%
“…GC retention times were considered in compound identification, and authentic standards were utilized when possible. In addition, compound identifications were based on information (GC retention times, and MS and IR spectra of authentic standards) from many previous studies conducted in this laboratory on volatiles in grains, breads, and wetted millet samples (Seitz et al 1993, Chang et al 1995, Seitz 1995.…”
Section: Testmentioning
confidence: 99%
“…GC retention times were considered in compound identification, and authentic standards were utilized when possible. In addition, compound identifications were based on information (GC retention times, and MS and IR spectra of authentic standards) from many previous studies conducted in this laboratory on volatiles in grains, breads, and wetted millet samples (Seitz et al 1993, Chang et al 1995, Seitz 1995.Because it was apparent that some compounds were only slightly separated, peaks recorded by MS and IR detectors were carefully evaluated by examining MS and IR spectra across the entire width of the peaks. Extracted ion (MS) and wavelength (IR) techniques were used to identify the exact locations of compounds in chromatograms.…”
mentioning
confidence: 99%
“…Sourness, a primary taste sensation (DeSimone et al, 2001), can be imparted by sourdough fermentation and is a desirable characteristic of many traditional African cereal foods (Nout, 2009). The sourness may also potentially mask the reported undesirable beany flavour of soya (Serrem et al, 2011a) and mousy flavour of pearl millet foods (Seitz et al, 1993). Further, sourdough fermentation reduces the level of phytate, a potential antinutrient, in whole grains (Katina et al, 2005) and may improve the texture of baked goods (Arendt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%